Efektywność deglomeracji zakładów przemysłowych w okręgach deficytowych pod względem siły roboczej - Nowicki, Zbigniew (Wydział Prawa i Administracji UAM, 1966)
The stipulations of a resolution passed by Economic Committee at the Council of Ministers in 1965 dealing with restraints which ought to be applied on the growth of employment by way of deglomeration, automatization and mechanization of industrial plants and construction enterprises situated in regions with a deficit of labour force — have obliged the regional industrial authorities to analyse the possibilities of deglomerating the plants from specific towns. The deglomeration should be undertaken only in the case if it is possible to prove its positive effects. The author maintains that a positive result of deglomeration depends on: 1) a proper selection of enterprises destined for deglomeration, 2) a strict precision of directions in which deglomeration will let itself be felt; their scope and hierarchy must not necessarily be the same in different regions, despite the same fundamental goal, that is to say, to restrain the growth of employment. The starting point in choosing the plants which qualify for deglomeration ought to be the examination of the balance of employment (with specified vocations). The plants ought to be classified according to how much they are bound with the region's economy. In order to measure the effect of deglomeration it is necessary, inter alia, to keep an account of production costs for the plant destined for deglomeration, which will take into consideration its present day and future localization.